COVID-19 pandemic - International events: protocols for organisation and participation (2021)
The global COVID-19 pandemic has significantly affected the world of sport. After many weeks of sporting inactivity, and sometimes of lockdown, the health conditions of some countries have stabilized, which leads to consider a gradual return to competitions with important adjustments which affect on the one hand the conditions of organization, and on the other hand the medical monitoring of the teams.